2018
DOI: 10.1152/jn.00340.2018
|View full text |Cite
|
Sign up to set email alerts
|

Ionic mechanisms underlying tonic and burst firing behavior in subfornical organ neurons: a combined experimental and modeling study

Abstract: Subfornical organ (SFO) neurons exhibit heterogeneity in current expression and spiking behaviour, where the two major spiking phenotypes appear as tonic and burst firing. Insight into the mechanisms behind this heterogeneity is critical for understanding how the SFO, a sensory circumventricular organ, integrates and selectively influences physiological function. To integrate efficient methods for studying this heterogeneity, we built a single-compartment, Hodgkin-Huxley type model of an SFO neuron that is par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Therefore, we explored which combination of these previously reported ion channel changes led to an increase of excitability in the APP/PS1 morphologies. In line with experimental findings, we found several ion channel changes that increased the overall spike rate and burst firing: down-regulation of I AHP (Beck and Yaari, 2008; Zhang et al ., 2014; Wang et al ., 2015a; Niday and Bean, 2021), up-regulation of I Na and persistent I Nap (Williams and Stuart, 1999; Yue et al ., 2005; Beck and Yaari, 2008; Liu et al ., 2015; Wang et al ., 2016; Ghatak et al ., 2019) and up-regulation of T-type calcium current I CaT (Yaari et al ., 2007; Beck and Yaari, 2008; Cain and Snutch, 2013; Medlock et al ., 2018; Garg et al ., 2021). Our simulations showed that, although ion channel modifications alone led to an increased firing of especially bursts ( Supplementary Figure S4C , Middle panel ), they did not reproduce quantitatively the output mode transition from single spiking to predominantly burst firing as reported in figure 1B of (Šišková et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we explored which combination of these previously reported ion channel changes led to an increase of excitability in the APP/PS1 morphologies. In line with experimental findings, we found several ion channel changes that increased the overall spike rate and burst firing: down-regulation of I AHP (Beck and Yaari, 2008; Zhang et al ., 2014; Wang et al ., 2015a; Niday and Bean, 2021), up-regulation of I Na and persistent I Nap (Williams and Stuart, 1999; Yue et al ., 2005; Beck and Yaari, 2008; Liu et al ., 2015; Wang et al ., 2016; Ghatak et al ., 2019) and up-regulation of T-type calcium current I CaT (Yaari et al ., 2007; Beck and Yaari, 2008; Cain and Snutch, 2013; Medlock et al ., 2018; Garg et al ., 2021). Our simulations showed that, although ion channel modifications alone led to an increased firing of especially bursts ( Supplementary Figure S4C , Middle panel ), they did not reproduce quantitatively the output mode transition from single spiking to predominantly burst firing as reported in figure 1B of (Šišková et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the voltage-dependent sodium channel INa in the axon (Liu et al ., 2015; Wang et al ., 2016; Ghatak et al ., 2019) was upscaled 1.3-fold and the persistent sodium channel INap in the soma (Williams and Stuart, 1999; Yue et al ., 2005; Beck and Yaari, 2008) was upscaled 2-fold in Figure 4E of Scenario 3 for extrinsic ( E/I balance) and intrinsic (ion channel) modifications. At the same time the medium afterhyperpolarisation calcium-activated potassium channel I AHP in the soma and apical dendrites was downscaled 0.85-fold (Beck and Yaari, 2008; Zhang et al ., 2014; Wang et al ., 2015b,a; Niday and Bean, 2021) in Figure 4E , while the T-type calcium channel in dendrites (Yaari et al ., 2007; Beck and Yaari, 2008; Cain and Snutch, 2013; Medlock et al ., 2018; Garg et al ., 2021) was upscaled 2-fold. For the effect of ion channel changes alone in Supplementary Figure S4C we scaled the aforementioned ion channel conductances to additional values (0.05 for I AHP and 3 for I Nap , I Na and I CaT ) in order to investigate a possible maximum burst firing increase (with minimal change in single spike firing) under pathological ion channel conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For AD‐related pathologies the L‐type Ca 2+ channel (Anekonda et al., 2011; Berridge, 2014), the A‐type K + channel (Chen, 2005) and Na + channels (Ghatak et al., 2019; Müller et al., 2021; Wang et al., 2016) have been shown to be involved in burst rate amplification. Modelling studies (Garg et al., 2021; Medlock et al., 2018) confirm the role of Ca 2+ channels for enhanced burst firing. Evidently, the modification of intrinsic excitability due to alterations in ion channel expression is well documented in AD.…”
Section: Introductionmentioning
confidence: 89%
“…The formulations of I Na , I K , and I L are the same as in the HH model. I Ca is formulated based on Medlock et al 31 with the addition of an inactivation gate. Eq.1 is numerically solved using a forward Euler method with Δ x = 0.045 cm and Δ t = 0.005 ms .…”
Section: Methodsmentioning
confidence: 99%